Rapid initiation of guided bone regeneration driven by spatiotemporal delivery of IL-8 and BMP-2 from hierarchical MBG-based scaffold. (March 2019) - Lin, Dan; Chai, Yanjun; Ma, Yifan; Duan, Bing; Yuan, Yuan; Liu, Changsheng
Abstract: Initiation of endogenous repair mechanisms, including key steps of stem cell recruitment and cartilage intermediate formation in endochondral ossification, is vital to regeneration of large bone defects. To biomimetically promote a rapid initiation and ensuing osteogenic stimulation, exogenous chemokine IL-8 and growth factor BMP-2 were orchestrated in a mesoporous bioactive glass (MBG)-based spatiotemporal delivery system, to achieve a rapid release of IL-8 followed by a long-term sustained release of BMP-2. The synergistic effect of IL-8 and BMP-2 on initiation stage of bone healing and underlying mechanism were thoroughly investigated in vitro and in vivo . Intriguingly, apart from its superiority in stem cell recruitment to BMP-2, IL-8 not only endowed a histological "prep-state" of endochondral ossification by up-regulating chondrogenic genes and inducing the formation of extensive cartilage tissues, facilitating rapid bone transformation by BMP-2, but also triggered a cellular "prep-state" with high expression of BMP receptors, enhancing the osteoinductivity of BMP-2. With the spatiotemporal delivery system, orchestrated signal stimuli of IL-8 and BMP-2 induced a rapid initiation including efficient stem cell recruitment and a "chondrogenic/osteogenic balance" at the first stage of endochondral ossification, and the scaffold facilitated sufficient osteoconductivity, together resulting in early extensive bone mineralization and an advanced regeneration throughout the repair of large bone defect. We believe this new idea could provide insights toward designing bone-repairing biomaterials with higher regenerative efficiency.